USABILTY EVALUATION OF IMCAT (INDIRECT MODEL CHECKING APPROACH FOR TRANSFORMATION) - ALIYU, ZIYAULHAQ (2015)
Indirect Mode Checking Approach for Transformation (IMCAT) was developed by one of the researchers at the Universiti Teknologi PETRONAS (UTP). It is the first verification approach that can verify Code Generator (a tool that transforms software model in to a code) where the person in charge of the verification does not have the transformation rules (source code) which enables IMCAT to verify different commercial CG. Usability evaluation is performed in order to identify the usability problem of an application/approach and provide suggestion to those problems for improvement. An application/approach is considered "usable" if it is easy to learn (learnability), easy to implement (efficiency) andbehaves as expected (effectiveness). IMCAT's developers focus on its features rather than its usability.